A low-complexity zero-forcing beamformer design for multiuser MIMO systems via a dual gradient method - Li, Bin; Dam, Hai Huyen Heidi; Cantoni, A. (American Institute of Mathematical Sciences, 2016)
© 2016 American Institute of Mathematical Sciences. All rights reserved.In this paper, we consider the zero-forcing beamforming (ZFBF) under the per-antenna power constraints (PAPC). Our objective is to maximize the minimum user information rate. Traditionally, ZFBF under PAPC with a max-min performance measure can be transformed into a second order cone problem and then solved by applying the interior point method. However, it is expensive to realize this design in practice due to high computational com-plexity per iteration. An alternative low complexity zero-forcing beamformer design is proposed for MU-MIMO systems by applying a dual gradient method. Different from the step size rule in the literature, a backtracking line search is adopted. A numerical example is provided to show the effectiveness of the proposed method.